Make it someone’s job: Documenting the growth of the academic integrity profession through a collection of position postings - Vogt, Lisa; Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2022)
We examine specific roles in higher education specializing in academic integrity. We collected publicly advertised job postings from 2018 to 2021 (N = 34) from Canada (n = 18), the United States (n = 14), and Australia (n = 2). Our review showed that academic integrity jobs can be situated within different units including student affairs, the library, or the teaching and learning centre among others. Salaries ranged from $49,000 CAD to over $100,000 CAD, with salaries in senior leadership positions generally not being listed in public postings. We conclude for academic integrity work to be recognized through dedicated positions and compensated in a manner that demonstrates the work is valued by the institution. We further call for increased professional learning and training opportunities for those whose work is specialized around academic integrity.